WRITTEN SOURCES IN THE REPERTOIRE OF THE CHRISTMAS CAROLS FROM THE TRANSYLVANIAN PLAIN - GERGELY, Zoltán (Studia Universitatis Babes-Bolyai Musica, 2022)
In the structure of the carols from the Transylvanian Plain has survived an old material of tunes and texts. The origin of some song’s dates back as far as the 16th century, and from that period to the 19th century the set of songs had been enriched with more and more tunes. In the material collected by the author an important style group is the Variants of the songs from the hymnals. The author argues that even if the written or printed forms still have their role in the learning, remembering, and singing of Christmas songs, the learning of new tunes or the passing of the old ones to the new generation happens by the well-known oral tradition and not with the help of music sheets.